Health Education About Uric Acid As An Effort To Increase Public Knowledge And Awareness In Tanjung Beringin Village, Dusun III - Emi Pebriani; Lisa Lestari; Nora Nur Indah Sari; Op Shella Yolangga; Reka Fitria; Rika Meinita; Saryulis Saryulis; Selina Febriyanti (Universitas Dehasen Bengkulu, 2026)
Gout is a degenerative disease that is commonly experienced by the community and can reduce quality of life if not properly managed. A lack of knowledge regarding risk factors, symptoms, and prevention of gout is one of the main contributors to the high incidence of this condition in the community. This community service activity aimed to improve public knowledge and awareness of gout through health education. A descriptive method with a participatory approach was applied through face-to-face counseling sessions. The activity was conducted in Tanjung Beringin Village, Hamlet III, from November 24 to December 22, 2025, involving 58 participants. Evaluation was carried out using pre-test and post-test questionnaires. The results showed an increase in participants’ knowledge after the counseling sessions, particularly regarding the causes, symptoms, prevention, and management of gout through healthy lifestyle practices. This activity demonstrates that health education is effective as a promotive and preventive effort to improve community health status. Therefore, gout health education should be implemented continuously and integrated with other community health programs.